2011
DOI: 10.1590/s1517-86922011000500004
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade funcional e força muscular respiratória de candidatos ao transplante hepático

Abstract: Introduction: Chronic liver disease results in large functional impact, causing loss of muscle mass and function with consequent reduction of functional capacity. Objective: To evaluate and compare the respiratory muscle strength and functional capacity of candidates for liver transplantation who are under Class B or C according to Child Pugh Score and to correlate these variables within each group. Methods -Cross-sectional study with a convenience sample of 35 patients divided into two groups based on the sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…In the present study, 22.5% of the individuals had liver cirrhosis and reduced values of the MIP, MEP, and distance traveled on the 6MWT. Pereira et al (2011) found that the respiratory muscle strength and exercise capacity of adults with hepatic cirrhosis were proportional to the severity of the disease and were lower in patients with more advanced cirrhosis than in those with less advanced disease. Patients with cirrhosis have hepatic insufficiency, which is commonly accompanied by several findings, such as decreased muscle mass (MANTANO-LOZA et al, 2012), changes in growth anddevelopment, andmalnutrition (FAINTUCH, 2000), besides lower synthesis of albumin and others proteins.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the present study, 22.5% of the individuals had liver cirrhosis and reduced values of the MIP, MEP, and distance traveled on the 6MWT. Pereira et al (2011) found that the respiratory muscle strength and exercise capacity of adults with hepatic cirrhosis were proportional to the severity of the disease and were lower in patients with more advanced cirrhosis than in those with less advanced disease. Patients with cirrhosis have hepatic insufficiency, which is commonly accompanied by several findings, such as decreased muscle mass (MANTANO-LOZA et al, 2012), changes in growth anddevelopment, andmalnutrition (FAINTUCH, 2000), besides lower synthesis of albumin and others proteins.…”
Section: Discussionmentioning
confidence: 92%
“…Many patients with chronic liver disease develop liver cirrhosis (PEREIRA et al, 2011), including cirrhosis-consequent disorders such as liver atresia, active chronic hepatitis, alfa 1 antitrypisin deficiency, Wilson's disease (DE BRITO et al, 2005;ROBERTS;SCHILSKY, 2008) and type IX glycogen storage disease (BURDA;HOCHULI, 2015). In the present study, 22.5% of the individuals had liver cirrhosis and reduced values of the MIP, MEP, and distance traveled on the 6MWT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that cirrhosis is a progressive disease, Pereira et al 33 state that the advancement of hepatic diseases tends to further reduce the functional capacity of those afflicted, because patients with a Child-Pugh score of C had worse performance on the 6MWT compared with patients with Child-Pugh scores of A and B. Recently, Pereira et al 34 demonstrated in a survivability analysis that individuals with cirrhosis who walk a distance smaller than 410 m had a survivability rate of 55%.…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al 6 pesquisaram 35 pacientes e mostraram que o progresso da doença hepática contribui para o aparecimento de várias complicações, que parecem favorecer a redução da capacidade funcional dos indivíduos. Esta pode ser medida por meio do teste de caminhada de seis minutos (TC6), um indicador da capacidade física global que tem o objetivo de avaliar pré e pós-intervenção médica e é um bom preditor de morbidade e mortalidade por doenças cardiorrespiratórias, bem como por complicações decorrentes de transplante de pulmão, coração e fígado.…”
Section: Introductionunclassified